Thermal comfort assessment of orthopaedic health professionals in an operating room - Nelson Rodrigues (2018)
The present work aims to study thermal sensation of orthopaedic health professionals during the execution of their activities in an operating room. The development of a questionnaire allowed the knowledge of the personal factors and thermal sensation of those professionals when exposed to their work environment. Considering the data similarities, four different classes were created: "Surgeon", "Surgeon's Assistant", "Instrumentalist" and "Nurses and Auxiliaries". Among the considered classes, the study focuses in two: "Surgeons" and "Nurses and Auxiliaries" which presented considerable differentiation. The first class presented a thermal sensation directed towards a hotter thermal sensation, while the latter on was directed to a colder thermal sensation. Additionally, it was verified that the surgeons present a greater intolerance towards thermal environment variations when compared to the nurses and auxiliaries.